Consumer green purchase behaviour among millennial generation - Nurul Amanina, Abdul Basir (2018)
The rapid growth of development in the economy for the last few decades has greatly increase consumers’ worldwide consumption and became the main cause that contribute to environmental degradation. Consequently, more people becoming increasingly aware and concerned about environmental issues especially among millennial generation. They are now demand for more environmental friendly products, hence many green marketers and manufacturers have shift the attention towards the importance of understanding the green purchase behaviour among this market segment. The purpose of this paper is to determine factors that have significant relationship toward millennial consumer’s green purchase behaviour in Malaysia by integrating the Theory of Planned Behaviour as research framework. The research model was adapted and modified from The Theory of Planned Behaviour (TPB) added with another potential variable namely, environmental involvement and media exposure to environmental message to identify the key factors that stimulate millennial consumer’s green purchase behaviour. A total of 375 questionnaires were distributed among UUM students by using proportionate sampling, to perform the statistical analysis for data analysis. Results showed attitude towards green products, subjective norm, perceived behavioural control, environmental involvement and media exposure to environmental message have significant effect toward millennial consumer’s green purchase behaviour. In addition, subjective norm was found to be the most influential factor that contribute to millennial consumer’s green purchase behaviour.